2013
DOI: 10.1021/pr4008255
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Levels of Circulating Immunoinflammation-Related Protein Complexes Are Associated with Cancer

Abstract: Disease-specific immune response-related protein complexes in the bloodstream are associated with disease status. We used proteomic technologies to screen novel circulating immunoinflammation-related protein complexes (IIRPCs) and to evaluate their diagnostic accuracy. The discovery study included 96 gastric cancer patients and 83 healthy controls and was designed to isolate and identify the IIRPCs. Then an independent validation study including 1366 patients with lung, colorectal, pancreatic, gastric, or thyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 31 publications
4
32
0
Order By: Relevance
“…Recently, emerging evidence indicates that changes in the glycosylation of total serum IgG isolated using Protein A or Protein G are associated with pathophysiological states 30 31 32 33 34 35 . In this study, we employ our developed approach to obtain DSIgG, which only exists in patients with chronic diseases 26 . Mass spectrometric analysis indicated that DSIgG is mainly composed of two subclasses of IgG1 and IgG2.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, emerging evidence indicates that changes in the glycosylation of total serum IgG isolated using Protein A or Protein G are associated with pathophysiological states 30 31 32 33 34 35 . In this study, we employ our developed approach to obtain DSIgG, which only exists in patients with chronic diseases 26 . Mass spectrometric analysis indicated that DSIgG is mainly composed of two subclasses of IgG1 and IgG2.…”
Section: Discussionmentioning
confidence: 99%
“…2 GC patients and 13 BGD patients without the information of sex or age were excluded before the native-PAGE separation. The remaining serum samples from 510 GC patients and 512 BGD patients were separated using an optimized native-PAGE as previously described 26 . It was found that 107 GC patients and 69 BGD patients had no IIRPCs and excluded in the following study 26 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations